2020
DOI: 10.1093/cid/ciaa1878
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of 2-Drug Regimens vs 3-Drug Regimens in Antiretroviral Treatment–Experienced People Living With Human Immunodeficiency Virus

Abstract: Background Limited data exist comparing clinical outcomes of two-drug regimens (2DRs) and three-drug regimens (3DRs) in people living with HIV. Methods Antiretroviral treatment-experienced individuals in RESPOND switching to a new 2DR or 3DR from 1/1/12-1/10/18 were included. The incidence of clinical events (AIDS, non-AIDS cancer, cardiovascular disease, end-stage liver and renal disease, death) was compared between regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The minimal biomarker changes observed are as expected, given similar outcomes in viral replication demonstrated in clinical trials that showed no significant difference in rates of virologic suppression, residual viremia, and viral blips with dolutegravir/lamivudine 2DR vs comparator 3/4DRs [ 17–20 , 22 ]. The clinical significance of these small fluctuations in inflammatory biomarkers is unknown and data have not demonstrated a difference in AIDS-related or non-AIDS-related clinical endpoints between 3/4DRs and 2DRs [ 39 , 40 ]. Changes in CD4 + /CD8 + ratio were similar between dolutegravir/lamivudine vs comparator postswitch in randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal biomarker changes observed are as expected, given similar outcomes in viral replication demonstrated in clinical trials that showed no significant difference in rates of virologic suppression, residual viremia, and viral blips with dolutegravir/lamivudine 2DR vs comparator 3/4DRs [ 17–20 , 22 ]. The clinical significance of these small fluctuations in inflammatory biomarkers is unknown and data have not demonstrated a difference in AIDS-related or non-AIDS-related clinical endpoints between 3/4DRs and 2DRs [ 39 , 40 ]. Changes in CD4 + /CD8 + ratio were similar between dolutegravir/lamivudine vs comparator postswitch in randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that individuals initiating 2-ART were older and had shorter time-to-discontinuation [ 30 ]. These differences, especially older age and more comorbidities, are also well established in recent real world comparisons [ 31 33 ]. The significantly higher proportion of renal disease, hemodialysis and bone disorders in the 2-ART cohort compared with 3-ART cohort might be a reason for the choice of NRTI-sparing regimen.…”
Section: Discussionmentioning
confidence: 84%
“…The role of cART in dyslipidemia is still not fully clear but could be partially explained by alteration of triglycerides hepatic synthesis and alterations of retinoic acid and LDLbinding proteins [45,46]. In any case, recently developed antiretroviral drugs, such as raltegravir, dolutegravir, bictegravir, rilpivirine and doravirine have a safer impact on lipid profile compared to older ones (such as zidovudine, stavudine, nevirapine, and partially lamivudine); two-drug combination regimens are also a modern therapeutic option that could permit, importantly, in selected PLWH, decrease of the pharmacological burden without losing efficacy in virological suppression [47,48].…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%